Marquinez Argote, G. (2000). Breve tratado del Cielo y los Astros del Maestro Javeriano Mateo Mimbela (1663-1736). Santafé de Bogotá: CEJA-UCAT. ISBN: 980-322-011-X. Número de páginas: 174. - Domínguez Miranda, Manuel (2014)
null